2018
DOI: 10.1038/s41598-018-26920-5
|View full text |Cite
|
Sign up to set email alerts
|

Carriage of critically important antimicrobial resistant bacteria and zoonotic parasites amongst camp dogs in remote Western Australian indigenous communities

Abstract: Camp dogs in indigenous communities in the Western Australian Kimberley Region, share the domestic environment with humans and have the potential to act as carriers of, and sentinels for, a wide range of zoonotic agents, including intestinal parasites and antimicrobial resistant bacteria. In this study, we investigated the carriage of extended-spectrum-cephalosporin-resistant (ESC-resistant) Escherichia coli, methicillin-resistant Staphylococcus aureus (MRSA) and species of hookworm and Giardia among camp dogs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 46 publications
3
13
1
Order By: Relevance
“…isolates in Australia in which the few MRSA isolated were predominantly hospital‐associated MRSA strains, most notably ST22‐IV (Worthing et al, ), probably a result of most clinical isolates originating from urban settings in dogs with a history of hospitalization. Importantly, our findings were similar to the findings of Rusdi et al () in the Kimberley region of Western Australia, who also detected PVL‐positive ST93 and ST5 from nasal swabs from dogs. This likely reflects demographic similarities between these two study populations—such as a living in a harsh physical environment, social disadvantage and geographical isolation—features which are frequently experienced in remote Aboriginal communities.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…isolates in Australia in which the few MRSA isolated were predominantly hospital‐associated MRSA strains, most notably ST22‐IV (Worthing et al, ), probably a result of most clinical isolates originating from urban settings in dogs with a history of hospitalization. Importantly, our findings were similar to the findings of Rusdi et al () in the Kimberley region of Western Australia, who also detected PVL‐positive ST93 and ST5 from nasal swabs from dogs. This likely reflects demographic similarities between these two study populations—such as a living in a harsh physical environment, social disadvantage and geographical isolation—features which are frequently experienced in remote Aboriginal communities.…”
Section: Discussionsupporting
confidence: 92%
“…All MRSA strains represented in this study are considered community‐associated lineages and have been associated with human clinical disease in Australia (Coombs & Daley, ). With the notable exception of a similar study in dogs in the Kimberley region of Western Australia, which also isolated MRSA from 2.6% of dogs (Rusdi et al, ), the prevalence of MRSA carriage in our study was higher than that reported in other studies worldwide, many of which have not isolated MRSA from community‐based dog population (predicated on outpatient well‐visit veterinary contact) (Daley et al, ; Gronthal et al, ) or have found the prevalence of MRSA carriage to be low (Loeffler et al, ; Weese & van Duijkeren, ). Our findings and those of Rusdi et al () present an important contrast with recent Australian studies which have failed to demonstrate carriage of MRSA in dogs or cats in urban settings (Bean & Wigmore, ; Worthing et al, ).…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…These ndings are in agreement with a recent study in two Sydney veterinary hospitals that isolated MRSP from 8% of veterinary personnel owned dogs and 7% of general canine hospital admissions (32). Other studies in non-clinical Australian settings have yielded much lower MRSP carriage estimates; only one MRSP was isolated from 117 healthy dogs in Victoria (33) and no MRSP on dogs from remote Aboriginal communities in Western Australia and New South Wales (34,35).While the Victorian and Sydney study did not detect MRSA in cats or dogs, the two studies on dogs from remote Aboriginal communities in Western Australia and New South Wales identi ed MRSA in 2.6% of the dogs (34,35). MRSA has been detected in Australian horses (3.7%) (2) so perhaps the lack of MRSA isolation in horses could be explained by the small sample size and single sampling location in this study, indicating the need to enrol more horses from multiple locations in future carriage investigations.…”
Section: Discussionsupporting
confidence: 90%